2022
DOI: 10.3390/ijms23063266
|View full text |Cite
|
Sign up to set email alerts
|

Differential Metabotypes in Synovial Fibroblasts and Synovial Fluid in Hip Osteoarthritis Patients Support Inflammatory Responses

Abstract: Changes in cellular metabolism have been implicated in mediating the activated fibroblast phenotype in a number of chronic inflammatory disorders, including pulmonary fibrosis, renal disease and rheumatoid arthritis. The aim of this study was therefore to characterise the metabolic profile of synovial joint fluid and synovial fibroblasts under both basal and inflammatory conditions in a cohort of obese and normal-weight hip OA patients. Furthermore, we sought to ascertain whether modulation of a metabolic path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 46 publications
2
25
2
Order By: Relevance
“…Skin is an important target tissue in PsA and therefore, we sought to explore the contribution of dermal fibroblasts -the main regulators of ECM homeostasis- in disease pathogenesis. Our transcriptomic analysis revealed that PsA fibroblasts exhibited greater proliferation and increased mitochondrial respiration compared to fibroblasts from HI, which could underpin their activated phenotype ( 49 , 50 ). Notably, PsA fibroblasts also displayed decreased expression of transcripts involved in TNFα signaling and IFN response, possibly shaping a counteracting immunosuppressive adaptation to the inflammatory microenvironment of the psoriatic skin.…”
Section: Discussionmentioning
confidence: 87%
“…Skin is an important target tissue in PsA and therefore, we sought to explore the contribution of dermal fibroblasts -the main regulators of ECM homeostasis- in disease pathogenesis. Our transcriptomic analysis revealed that PsA fibroblasts exhibited greater proliferation and increased mitochondrial respiration compared to fibroblasts from HI, which could underpin their activated phenotype ( 49 , 50 ). Notably, PsA fibroblasts also displayed decreased expression of transcripts involved in TNFα signaling and IFN response, possibly shaping a counteracting immunosuppressive adaptation to the inflammatory microenvironment of the psoriatic skin.…”
Section: Discussionmentioning
confidence: 87%
“…Second, in actual conditions, hip joint implants are lubricated with synovial fluid, which is a natural human joint lubricant. Unfortunately, the current model still maintains dry contact by negating the influence of the synovial fluid 45,46 . Next, the materials used-SS 316L and UHMWPE-are assumed to be linearly elastic.…”
Section: Discussionmentioning
confidence: 97%
“…Synovial joint tissue ( n = 32) was collected peri‐operatively and used to isolate and characterise primary SF as previously described. 16 , 24 , 25 Each joint sample collected was from an independent patient undergoing arthroscopy at a single anatomical joint, see Supplementary Materials (SM. 1 ) for the summary of patient characteristics.…”
Section: Methodsmentioning
confidence: 99%